2018
DOI: 10.31195/ejejfs.476504
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting in Turkey: Challenges and opportunities in future

Abstract: Turkey has been undergoing positive agricultural transformations since the 2011. Its agricultural sector today is developing new techniques and products. One of the best examples of this is the production of vermicompost and its use in agriculture. Turkey is on both Asian and European continents (Eurasia) with approximately 81 million people. Turkey has 24 million hectares of agriculture land (excluding pastures+ meadows, including total arable land and under permanent crops). However, there is little data ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
12
0
4
Order By: Relevance
“…As well as, B.M. were caused not only dissolving P and K, fix the atmospheric N, but also stimulate the growth regulators and hormones "auxins, cytokinins and gibberellins" production to enhance the beneficial microbes "microbial communities" to inhibit the soil borne pathogens (Birla et al, 2018;Bellitürk, 2018;Al Ali et al, 2019 andSoraya et al, 2020) and increase plant defense, healthy growth and quality food. These are agreement with (Ragab et al, 2016;Lyngdoh et al, 2017;Piya et al, 2018;Htwe et al, 2019 andUmadevi et al, 2019).…”
Section: Vegetation Pod Yield and Its Componentsmentioning
confidence: 99%
“…As well as, B.M. were caused not only dissolving P and K, fix the atmospheric N, but also stimulate the growth regulators and hormones "auxins, cytokinins and gibberellins" production to enhance the beneficial microbes "microbial communities" to inhibit the soil borne pathogens (Birla et al, 2018;Bellitürk, 2018;Al Ali et al, 2019 andSoraya et al, 2020) and increase plant defense, healthy growth and quality food. These are agreement with (Ragab et al, 2016;Lyngdoh et al, 2017;Piya et al, 2018;Htwe et al, 2019 andUmadevi et al, 2019).…”
Section: Vegetation Pod Yield and Its Componentsmentioning
confidence: 99%
“…of vermicompost and vermitea (4 times as a soil drench).In the same trend Al Ali et al (2019), gave that organic applications had a significant (p<0.05) on eggplant yield and plant vegetation growth, so that the highest yield at organic fertilizers and the lowest total yield at chemical fertilizers. In the same line many researchers, (Seethalakshmi, 2011;Gandhi and Sundar, 2012;Sundararasu and Jeyasankar, 2014;Singh and Hussain, 2015and Piya et al, 2018and Bellitürk, 2018 reported that. They found the use of vermicompost improves the soil aggregates, bulk density, water holding capacity, organic matter, maro and micronutrients, microbial properties (enzymes and microbial population).…”
Section: Chemical Composition In Shoots and Fruitsmentioning
confidence: 67%
“…Vermitea can be economically, productivity suitable for healthy plant growth, increased the fruit quality, yield and for enhancement the soil environment (Gandhi and Sundari, 2012;Sundararasu and Jeyasankar, 2014and Belliturk et al, 2017and Soraya et al, 2020.These reported that, significant increases in growth and yield of treated plants with vermitea, due to high available amounts of macro and micro-elements in vermitea. Positive effect of vermicompost at 5t/ha either or combination with FYM or chemical fertilizers lead to enhance the vegetation, flowering, fruiting stage, total yield and food quality of eggplants (Seethalakshmi,2011and Chaulagain et al,2017and Bellitürk, 2018. Similarly, Al Ali et al (2019), reported that organic fertilizers e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solucan gübrelerindeki yararlı mikroorganizmaların biyolojik aktivitesinin topraktakinden 10 ila 20 kat daha fazla olduğu belirtilmiştir (Edwards 1995). Organik içerikli biogübre, sağlıklı ve sürdürülebilir toprak anlayışını desteklemesi açısından kimyasal gübrelere iyi bir alternatif olarak gündeme gelmektedir (Bellitürk 2018, Bellitürk et al 2017, Mengistu et al 2017. Ek olarak Sinha et al (2010), kimyasal gübrelerin yerine vermikompost kullanımının "İkinci Yeşil Devrim" olarak nitelendirilebileceğini belirtmiştir.…”
Section: Sonuçlarunclassified